1995
DOI: 10.1164/ajrccm.151.6.7767542
|View full text |Cite
|
Sign up to set email alerts
|

Increased airway responsiveness to inhaled methacholine in a rat model of chronic bronchitis.

Abstract: Chronic exposure of rats to high concentrations of SO2 gas causes pathologic changes in airway similar to those seen in human chronic bronchitis. The purpose of this study was to examine the pulmonary mechanical correlates of these changes and to quantify the extent of mucous hypersecretion by measuring changes in mucous glycoproteins. Female Sprague-Dawley rats were exposed to 250 ppm SO2 gas, 5 h/d, 5 d/wk, for a period of 4 wk. Control rats were exposed to air only. On the day after the last SO2 exposure, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 18 publications
3
48
0
1
Order By: Relevance
“…The present study that included 40 healthy toll collectors showed an increased large airway wall thickness (tracheal wall thickness in this case) related to the working duration. Similar to the results of the present study, in animal models exposure to SO 2 (the most important air pollutant) caused hypertrophy of tracheal submucosal glands, and airway epithelial mucous cell hyperplasia and metaplasia 16,17) .…”
Section: Discussionsupporting
confidence: 91%
“…The present study that included 40 healthy toll collectors showed an increased large airway wall thickness (tracheal wall thickness in this case) related to the working duration. Similar to the results of the present study, in animal models exposure to SO 2 (the most important air pollutant) caused hypertrophy of tracheal submucosal glands, and airway epithelial mucous cell hyperplasia and metaplasia 16,17) .…”
Section: Discussionsupporting
confidence: 91%
“…The model of CB was developed by exposing the rats to a target concentration of 250 ppm of sulfur dioxide (5 hr/day, 5 days/week for 6 weeks), as previously described (5,6,8). Briefly, SO 2 of known concentration was obtained from a cylinder, diluted with air, and fed into the exposure chamber at a constant rate (7.6 ft 3 /min).…”
Section: Methodsmentioning
confidence: 99%
“…The acute symptoms of mucus hypersecretion, as in chronic bronchitis, can be modeled by exposure of rats to ozone or sodium metabisulfite (Murlas and Roum, 1985;Shore et al, 1995). Features of severe asthma (goblet cell hyperplasia, AHR, and eosinophilic airway infiltration) have been mimicked by chronic antigen exposure of atopic mice and guinea pigs (Blyth et al, 1998;Danahay and Broadley, 1998).…”
mentioning
confidence: 99%